Hemodynamic and respiratory implications of high intra-abdominal pressure during HIPEC. Issue 10 (October 2020) - Reis, Artur C V; Kusamura, Shigeki; Azmi, Norfarizan; Fumagalli, Luca; Piccioni, Federico; Valenza, Franco; Baratti, Dario; Guaglio, Marcello; Cavalleri, Adalberto; Garrone, Giulia; Barretta, Francesco; Deraco, Marcello
Abstract: Background: cytoreduction surgery (CRS) and heated intraperitoneal chemotherapy (HIPEC) is currently the standard of care for some peritoneal surface malignancies. There is experimental evidence supporting that high Intra Abdominal Pressure (IAP) during HIPEC could enhance the uptake of drugs by tumor tissues. However, few papers are describing the hemodynamic and respiratory effects of increased IAP during HIPEC. Aims: to evaluate the hemodynamic and respiratory association with different IAPs during HIPEC. Methods: This is part of an IRB board approved prospective randomized controlled trial conducted at The National Tumor Institute of Milan from 2014 to 2017 (NCT0294979). Patients diagnosed with Pseudomyxoma (PMP) or Peritoneal Metastasis of Colorectal Cancer (PM-CRC) were submitted to CRS and then randomized to receive low IAP (8–12 mmHg) or high IAP (18–22 mmHg) HIPEC. Hemodynamic and respiratory data were collected in eight different time-points during the whole procedure. Results: 33 patients (n low = 15, n high = 18) with PM-CRC and PMP were analysed. The mean IAP in the low IAP HIPEC group was 11.4 mmHg (SD: 2.5) and 18.1 mmHg (SD: 2.5) in the high IAP HIPEC group (p«0.001). There was no difference in the hemodynamic parameters between both groups, except for the central venous pressure (CVP) that was significantly higher in the high IAP group (p = 0.006). High IAP was well tolerated in the experimental arm with no hemodynamic and ventilation instability observed during the intervention. Conclusion: We conclude that high IAP at the level of 18–22 mmHg during HIPEC has no significant hemodynamic parameters difference, being feasible and safe in our study.